Pesantren Tradisional Sebagai Basis Pembelajaran Nahwu Dan Sharaf Dengan Menggunakan Kitab Kuning - Aliyah Aliyah (Universitas Islam Negeri Palangka Raya, 2018)
Traditional Islamic boarding school or pesantren is one of the oldest educational institutions in Indonesia, this is the center of the development of religious science, with books that use Arabic or called as the yellow book as the material being taught, to understand these books the students are taught first nahwu and sharaf or grammar as the science of tools to read, understand and interpret the contents of these books.Seeing the important role of nahwu and sharaf in understanding religious sources, especially the Qur'an and hadits, the purpose of writing this article is: 1) the role of pesantren as a center for the development of religious knowledge, 2) the books of nahwu and sharaf taught in pesantren , 3) nahwu and sharaf learning methods.This study uses the literature method, by examining several sources related to pesantren and learning nahwu and shraf by using the yellow books. This article concludes that the pesantren in the early days of the emergence of indeed the center of the development of religious science which originated in Arabic or yellow books, in pesantren the learning of nahwu and sharaf is the basis of the first knowledge taught because with this knowledge is the initial capital for the santri in understanding the other books, the books of nahwu and sharaf are taught, for the books of nahwu including,